Frictional half plane contacts subject to varying normal load and bulk tension under various load paths with application to fretting fatigue experiments - Truelove, J; Blades, LE; Hills, DA; Paynter, RJH (Elsevier, 2023)
In many fretting fatigue experiments the loads applied to the contact are sinusoidal and in phase, creating a straight line path through load space. Although this form of loading is a good representation of many of the load histories present in engineering assemblies, the usefulness of this form of load cycle when investigating the causes of fretting fatigue damage is limited. In this paper we first review solutions for uncoupled half plane contacts under bulk tension and normal loading, then develop some novel load paths with properties that are desirable in fretting fatigue experiments. Throughout this paper the results are illustrated via application to a Hertzian contact, although the principles apply to any contact capable of representation using half-plane theory.